Diagnostic Values of Ki67, Cox2, CD31, E-cadherin, VEGF, MMP2, and MMP9 Protein Expression in Human Melanoma - Karkhaneh Yousefi, Nahid; Muhammadnejad, Ahad; Rahmati, Marveh; Ghanadan, Alireza; Razavirad, Amirhossein (Asian Pacific Journal of Cancer Biology, 2024)
Background: Cutaneous melanoma, the most severe form of skin cancer, has an unpredictable behavior and a high mortality rate. Recent research has identified new biomarkers and their associations with certain histopathological features, offering essential insights into diagnosis, prognosis, and therapeutic strategies. Material and method: In this meticulously designed and executed study, we analyzed 85 formalin-fixed, paraffin-embedded (FFPE) tissue samples using the gold standard technique of immunohistochemistry (IHC) to characterize the protein expression profiles. We used a comprehensive panel of Ki67, Cox2, CD31, VEGF, MMP2, MMP9, and E-cadherin antibodies. Clinical stages were meticulously determined according to TNM classification, the thickness of the Breslow depth, and Clark levels. We employed robust statistical methods such as one-way ANOVA and curve estimation regression to analyze the data. The STRING database, a trusted resource, was used to identify protein-protein interactions and related pathways. Results: The results of our study unveiled novel pairwise positive correlations between CD31 and Ki67 (r = 0.72), and between VEGF and Ki67 protein expression (r = 0.63). We also found a significant inverse relationship between the expression of E-cadherin and some biomarkers, such as Ki67, CD31, and VEGF (p < 0.001 for all). Additionally, our findings revealed a strong positive association between the extent of tumor invasion and the expression levels of Ki67, CD31, and VEGF. The overexpression of these proteins was significantly correlated with advanced clinical stages (p < 0.001 for all). Conclusion: Our study suggests that the biomarkers we examined could be reliable potential diagnostic and prognostic biomarkers for cutaneous melanoma. These findings have the potential to significantly impact the diagnosis, prognosis, and treatment of this deadly disease, offering new avenues for improved patient care.